A subregional analysis of family change: The spatial diffusion of one‐parent families across Italian municipalities, 1991–2011. Issue 4 (7th April 2019) - Caltabiano, Marcantonio; Dreassi, Emanuela; Rocco, Emilia; Vignoli, Daniele
Abstract: This paper documents the expansion of new family patterns in Italy by scrutinising the spatial diffusion of one‐parent families across Italian municipalities for the period 1991–2011. We apply a hierarchical Bayesian model to the data of the last three Italian Population Censuses, acknowledging that variation cannot be broken down into temporal and spatial effects because space–time interaction is at the very heart of family changes. Our results illustrate substantial subregional and sub‐provincial heterogeneities in the spatial organisation of family systems, patterns that might have gone undetected had larger territorial units of analysis been considered. In addition, we show that especially socio‐economic factors were associated to the diffusion of new family forms. This paper challenges international scholarship that caricatures Italy as a monolithic, homogeneous family‐oriented country.